Correctional Institution Policy on Extraordinary Permission for Inmates Outside Visiting Hours - Tamara Cecilia Munthe; Abdul Razak Nasution; Mhd. Azhali Siregar (CERED Indonesia Institute, 2025)
In the course of legal proceedings, detainees held in detention centers retain certain rights as part of the protection and services afforded to them, including the right to apply for temporary leave and extraordinary leave. However, there is a distinction between temporary leave and extraordinary leave for detainees in detention centers. This differs from the situation of convicted prisoners, as prisoners are already serving their criminal sentences, and the detention center bears a fuller obligation to fulfill their rights compared with detainees who are still undergoing legal proceedings. Therefore, temporary leave and extraordinary leave may still be granted to detainees or prisoners, provided that the applicable legal procedures and regulations are observed.